PROSES SEMISOLID FORMING - Surojo, Eko; Suprihanto, Agus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2001)
This paper presents a semisolid forming process as a new process that can replace conventional casting andforming process. Semisolid forming process is metal procesing in semisolid state. There are several advantages of thisprocess. The important of these is non-turbulent filling of the die. Non-turbulent die fill in the process can eliminate airentrapment encountered in the conventional die casting. The semisolid forming process also offers the near net shapecapabilities of die casting and produces parts with less shrinkage porosity and macrosegregation. The limitation ofsemisolid forming process is this process requires globular (non-dendritic) structure alloys for raw material process.